Un projet de paysage intercommunal comme terrain de coopération territoriale - Benjamin Chambelland (Développement Durable et Territoires)
The article presents a current doctoral research led within the framework of an Industrial Agreements for Training through research alongside four public authorities situated in the Bordeaux Metropolis. The thesis is based on the support of a landscape project aiming to set up the management of a series of parks and gardens grouped under the term « Parc des Coteaux » (The Hillside Parks) – 240 ha. This experience reveals the interrelations in the work between the various stakeholders of this project (elected representatives, department heads, city gardeners, landscape architects, urban planners, ecologists and users). These articles enabled the deconstruction of the underlying representations in landscaping policies and bring to light the necessity of a territorial cooperation based on the long-term implication of the concerned stakeholders and to propose to structure a solutions research plan.